Preparation method of hollow nano zirconium oxide

Through nanohard template method and supergravity rotary filling bed technology, hollow nanozirconia with stable structures was prepared, which solved the problems of long preparation cycle and high cost in the existing technology, and achieved flexible regulation of particle size and wall thickness, which was suitable for Large-scale production and improved product performance.

CN119306251APending Publication Date: 2025-01-14BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310870199.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-14
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing hollow zirconia preparation methods have problems such as long preparation cycle, high cost and low yield, which limits its application in the fields of heat insulation, pollutant adsorption and catalyst support.

Method used

Using nano-hard template method combined with supergravity rotary filling bed technology, the hydrolysis and condensation process of zirconium salt is controlled by rapidly mixing zirconium salt solution and hard template suspension, and the structure-stable hollow nanozirconium oxide is prepared to achieve particle size and wall thickness. Flexible regulation.

Benefits of technology

Fast and low-cost hollow nanozirconia preparation is achieved, solving the problems of long preparation cycle and high cost in traditional methods, suitable for large-scale production, and improving the application performance of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306251A_ABST
    Figure CN119306251A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of hollow nano zirconium oxide, which comprises the following steps: S1, dissolving zirconium salt in an alcohol solvent to obtain a zirconium salt solution A; the method comprises the following steps: mixing a hard template, water and an alcohol solvent to obtain a suspension A; s2, introducing the zirconium salt solution A and the suspension A into a supergravity reactor through a peristaltic pump to realize rapid mixing reaction, and collecting a generated suspension B; filtering the suspension B, and washing with water to obtain a filter cake A; s3, drying the filter cake A, heating, pickling, washing with water, and drying to obtain hollow nano zirconium oxide; the hollow nano zirconium oxide prepared by the method can inherit the particle shape of the nano hard template, hollow nano zirconium oxide particles of 10-300nm are formed, and the flexible regulation and control of the wall thickness of the hollow nano zirconium oxide are realized by adjusting the dosage of the nano hard template.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of hollow zirconium oxide materials; more specifically, to a method for preparing hollow nano zirconium oxide. Background Art

[0002] Zirconia has good thermochemical stability, high-temperature electrical conductivity, high strength and toughness, as well as good mechanical, thermal, electrical and optical properties. It is an inorganic non-metallic material with excellent properties such as acidity and alkalinity and redox properties. Hollow zirconia combines the performance characteristics of hollow structural materials and zirconia materials. Compared with traditional solid phase materials, hollow structural materials have lower density, higher specific surface area and surface permeability. Due to the particularity of its structure and materials, hollow zirconia has great application prospects in the fields of thermal insulation, pollutant adsorption, catalyst carriers, etc.

[0003] The preparation methods of hollow zirconia include hard template method, soft template method, hydrothermal method, spray drying method, arc method, etc. The hard template method can accurately replicate the morphology of the template, which is convenient for the controllable study of the size and structure of hollow nanomaterials, and has attracted widespread attention. Pablo et al. (Arnal. PM, Weidenthaler. C, F. Schüth. Chemistry of Materials. 2006, 18, 2733-2739.) used SiO 2 As a hard template, zirconium n-butoxide was used as a zirconium source and hydrolyzed and polymerized in an ethanol solvent to form a coating on the core surface. The hydrated zirconium oxide was crystallized into oxides by calcination. After removing the nano-silica template with alkali solution, hollow zirconia microspheres with a diameter of 250nm were finally obtained. Yao et al. (Yao.H, Jia.D, Zhang.H.Ceramics International.2015,41,1531-1534.) used PSA microspheres as hard templates, placed the surface-modified template spheres in an ethanol solution of zirconium oxychloride, heated ammonia water in a water bath, and reacted ammonia vapor with zirconium oxychloride. The continuously generated white precipitate slowly deposited on the modified PSA spheres. After subsequent treatment, hollow zirconia microspheres with a diameter of 3μm were obtained. Guo et al. (Guo.CY, Hu.P, Yu.LJMaterials Letters.2009,63,1013-1015.) used carbon spheres as hard templates and synthesized C-Zr(OH) by precipitation on their surfaces with ammonia water. 4The core-shell heterogeneous structure was prepared by calcining and removing the template to prepare hollow zirconia microspheres with an average diameter of about 500nm and a shell thickness of about 50nm. The hollow zirconia material prepared by the hard template has a relatively simple preparation process and convenient morphology control, but has problems such as long preparation cycle, high preparation cost, and low yield, which limits the application and large-scale production of hollow zirconia materials. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing hollow nano-zirconia. The method utilizes a nano-hard template method and adopts a supergravity rotating packed bed, and cooperates with various raw materials and parameters to prepare a hollow nano-zirconia with a stable structure; the hollow nano-zirconia prepared by this method can inherit the particle shape of the nano-hard template, forming hollow nano-zirconia particles with a particle size of 10-300nm, and by adjusting the amount of the nano-hard template, the wall thickness of the hollow nano-zirconia can be flexibly controlled; the method solves the problem that continuous preparation cannot be achieved in the traditional hollow zirconia preparation method, and gives the product higher application performance and added value. The preparation method has rapid reaction, simple operating conditions, low raw material cost, and is easy to scale production.

[0005] To solve the above technical problems, the first technical solution adopted is as follows :

[0006] A method for preparing hollow nano zirconium oxide comprises the following steps:

[0007] S1, dissolving a zirconium salt in an alcohol solvent to obtain a zirconium salt solution A; mixing a hard template, water, and an alcohol solvent to obtain a suspension A;

[0008] S2, passing the zirconium salt solution A and the suspension A into a supergravity reactor through a peristaltic pump to achieve rapid mixing reaction, and then collecting the generated suspension B; filtering the suspension B, and washing with water to obtain a filter cake A;

[0009] S3, drying the filter cake A, heating it to 150-250°C for heat treatment for 0.5-1.5h, pickling it with sufficient hydrochloric acid with a concentration of 5-37% for 3-12h, washing it with water, and drying it to obtain hollow nano zirconium oxide;

[0010] According to certain embodiments of the present invention, in step S1, the zirconium salt is one or more of zirconium n-propoxide, zirconium isopropoxide, zirconium n-butoxide, and zirconium tert-butoxide; and the concentration of the zirconium salt is 0.02-0.1 mol / L.

[0011] According to some embodiments of the present invention, in step S1, the alcohol solvent is one or more of methanol, ethanol, n-propanol, isopropanol, tert-butanol, and sec-butanol.

[0012] According to some embodiments of the present invention, in step S1, the molar ratio of water to zirconium salt in the suspension A is 2:1-16:1.

[0013] According to certain embodiments of the present invention, in step S1, the hard template is one or more of nano-calcium carbonate, nano-magnesium carbonate, nano-lanthanum carbonate, nano-iron oxide, nano-aluminum oxide, nano-copper oxide, nano-zinc oxide, and nano-lanthanum hydroxide.

[0014] According to certain embodiments of the present invention, in step S1, the mass ratio of the hard template in the suspension A to the mass ratio when the zirconium salt is completely converted into zirconium oxide is 10:0.1-10:10.

[0015] According to some embodiments of the present invention, in step S2, the rotation speed of the ultra-gravity reactor is 300-3000 rpm.

[0016] According to certain embodiments of the present invention, in step S2, the feed flow rate of the peristaltic pump is 100-600 mL / min; and the feed flow rate ratio of the zirconium salt solution A and the suspension A in the peristaltic pump is 100:75-100:200.

[0017] According to certain embodiments of the present invention, in step S3, the acid is one or more of hydrochloric acid, nitric acid, acetic acid, and phosphoric acid.

[0018] In order to solve the above technical problems, the second technical solution adopted by the present invention is as follows :

[0019] A method for preparing hollow nano zirconium oxide comprises the following steps:

[0020] S1, mixing a zirconium salt and a hard template, dissolving them in water to obtain a zirconium salt suspension B; mixing an alkali and water to obtain an alkali solution A;

[0021] S2, passing the zirconium salt suspension B and the alkali solution A into the supergravity reactor through a peristaltic pump to achieve rapid mixing reaction, and then collecting the generated suspension C; washing the suspension C to obtain the filter cake B;

[0022] S3. After drying the filter cake B, calcining it at 500-800° C. for 3-7 hours to obtain hollow nano zirconium oxide.

[0023] According to certain embodiments of the present invention, in step S1, the zirconium salt is one or more of zirconium oxychloride, zirconium chloride, zirconium acetate, zirconium acetylacetonate, zirconium oxynitrate, and zirconium sulfate; and the concentration of the zirconium salt is 0.01-0.05 mol / L.

[0024] According to certain embodiments of the present invention, in step S1, the hard template is one or more of nano-carbon balls, nano-PS balls, nano-PSA balls, and nano-PMMA balls; the mass ratio of the hard template in the zirconium salt suspension B to the mass ratio when the zirconium salt is completely converted into zirconium oxide is 10:0.1-10:10.

[0025] According to some embodiments of the present invention, in step S1, the base is one or more of ammonia water, hydrazine hydrate, urea, ammonium bicarbonate, and potassium hydroxide; and the concentration of the base is 0.01-0.2 mol / L.

[0026] According to some embodiments of the present invention, in step S2, the rotation speed of the ultra-gravity reactor is 300-3000 rpm.

[0027] According to certain embodiments of the present invention, in step S2, the feed flow rate of the peristaltic pump is 100-600 mL / min; and the feed flow rate ratio of the zirconium salt suspension B to the alkali solution A in the peristaltic pump is 100:75-100:200.

[0028] Any range described in the present invention includes the end value and any numerical value between the end values ​​and any sub-range formed by the end value or any numerical value between the end values.

[0029] Unless otherwise specified, all raw materials in the present invention can be purchased from the market, and the equipment used in the present invention can adopt conventional equipment in the relevant field or refer to the existing technology in the relevant field.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1) The present invention uses ultra-gravity technology for the first time in combination with various raw materials and parameters to prepare structurally stable hollow nano-zirconium oxide. The excellent mass transfer capacity of the ultra-gravity reactor is utilized to effectively control the hydrolysis and condensation process of the zirconium salt, ensuring that the zirconium salt only undergoes heterogeneous nucleation on the surface of the nano-hard template, thereby achieving a rapid coating process.

[0032] 2) The preparation method of the present invention can flexibly control the wall thickness and particle size of the hollow nano-zirconia by changing the amount and size of the template; hollow nano-zirconia with different crystal phases can be synthesized, giving the product higher application performance and added value.

[0033] 3) The raw materials of the present invention are easy to obtain, low in cost, non-toxic, and the preparation process has low energy consumption, low cost, simple process, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The specific embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.

[0035] Figure 1This is a TEM image of the hollow nano-zirconia prepared in Example 1;

[0036] Figure 2 This is the X-ray diffraction pattern of the hollow nano-zirconia prepared in Example 1;

[0037] Figure 3 This is a TEM image of the nano-calcium carbonate used in the preparation process of Example 1;

[0038] Figure 4 This is a TEM image of the hollow nano-zirconia prepared in Example 2;

[0039] Figure 5 This is a TEM image of the hollow nano-zirconia prepared in Example 3;

[0040] Figure 6 This is a TEM image of the hollow nano-zirconia prepared in Example 4;

[0041] Figure 7 This is the X-ray diffraction pattern of the hollow nano-zirconia prepared in Example 5;

[0042] Figure 8 This is a TEM image of the hollow nano-zirconia prepared in Example 6;

[0043] Fig. 9 TEM image of the nano-carbon spheres used in the preparation process of Example 6;

[0044] Fig.10 This is a TEM image of the hollow nano-zirconia prepared in Example 7;

[0045] Fig.11 This is a TEM image of the product prepared in Comparative Example 1;

[0046] Fig.12 This is a TEM image of the product prepared in Comparative Example 2;

[0047] Fig.13 This is a TEM image of the product prepared in Comparative Example 3;

[0048] Fig.14 This is a TEM image of the product prepared in Comparative Example 4;

[0049] Fig.15 This is a TEM image of the product prepared in Comparative Example 5;

[0050] Fig.16 This is the X-ray diffraction pattern of the product prepared in Comparative Example 5;

[0051] Fig.17 This is a TEM image of the product prepared in Comparative Example 6;

[0052] Fig.18 This is a TEM image of the product prepared in Comparative Example 7;

[0053] Fig.19 This is a TEM image of the product prepared in Comparative Example 8;

[0054] Fig. 20 This is the TEM image of the product prepared in Comparative Example 9. DETAILED DESCRIPTION

[0055] In order to explain the present invention more clearly, the present invention is further described below in conjunction with embodiments. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0056] As one aspect of the present invention, a method for preparing hollow nano-zirconia comprises the following steps:

[0057] S1, dissolving a zirconium salt in an alcohol solvent to obtain a zirconium salt solution A; mixing a hard template, water, and an alcohol solvent to obtain a suspension A;

[0058] S2, passing the zirconium salt solution A and the suspension A into a supergravity reactor through a peristaltic pump to achieve rapid mixing reaction, and then collecting the generated suspension B; filtering the suspension B, and washing with water to obtain a filter cake A;

[0059] S3, drying the filter cake A, heating it to 150-250°C for heat treatment for 0.5-1.5h, pickling it with sufficient hydrochloric acid with a concentration of 5-37% for 3-12h, washing it with water, and drying it to obtain hollow nano zirconium oxide with amorphous crystal phase;

[0060] In certain embodiments of the present invention, in step S1, the zirconium salt is one or more of zirconium n-propoxide, zirconium isopropoxide, zirconium n-butoxide, and zirconium tert-butoxide; and the concentration of the zirconium salt is 0.02-0.1 mol / L.

[0061] In certain embodiments of the present invention, in step S1, the alcohol solvent is one or more of methanol, ethanol, n-propanol, isopropanol, tert-butanol, and sec-butanol.

[0062] In certain embodiments of the present invention, in step S1, the molar ratio of water to zirconium salt in the suspension A is 2:1-16:1.

[0063] In certain embodiments of the present invention, in step S1, the hard template is one or more of nano-calcium carbonate, nano-hydroxyapatite, nano-iron oxide, nano-aluminum oxide, and nano-zinc oxide.

[0064] In certain embodiments of the present invention, in step S1, the mass ratio of the hard template in the suspension A to the mass ratio when the zirconium salt is completely converted into zirconium oxide is 10:0.1-10:10.

[0065] In certain embodiments of the present invention, in step S2, the rotation speed of the high gravity reactor is 300-3000 rpm.

[0066] In certain embodiments of the present invention, in step S2, the feed flow rate of the peristaltic pump is 100-600 mL / min; and the feed flow rate ratio of the zirconium salt solution A and the suspension A in the peristaltic pump is 100:75-100:200.

[0067] In certain embodiments of the present invention, in step S3, the acid is one or more of hydrochloric acid, nitric acid, acetic acid, phosphoric acid

[0068] In order to solve the above technical problems, the second technical solution adopted by the present invention is as follows :

[0069] A method for preparing hollow nano zirconium oxide comprises the following steps:

[0070] S1, mixing a zirconium salt and a hard template, dissolving them in water to obtain a zirconium salt suspension B; mixing an alkali and water to obtain an alkali solution A;

[0071] S2, passing the zirconium salt suspension B and the alkali solution A into the supergravity reactor through a peristaltic pump to achieve rapid mixing reaction, and then collecting the generated suspension C; washing the suspension C to obtain the filter cake B;

[0072] S3. After drying the filter cake B, calcining it at 500-800° C. for 3-7 hours to obtain a hollow nano zirconium oxide having a tetragonal crystal phase.

[0073] In certain embodiments of the present invention, in step S1, the zirconium salt is one or more of zirconium oxychloride, zirconium chloride, zirconium acetate, zirconium acetylacetonate, zirconium oxynitrate, and zirconium sulfate; and the concentration of the zirconium salt is 0.01-0.05 mol / L.

[0074] In certain embodiments of the present invention, in step S1, the hard template is one or more of nano-carbon balls, nano-PS balls, nano-PSA balls, and nano-PMMA balls; the mass ratio of the hard template in the zirconium salt suspension B to the mass ratio when the zirconium salt is completely converted into zirconium oxide is 10:0.1-10:10.

[0075] In certain embodiments of the present invention, in step S1, the base is one or more of ammonia water, hydrazine hydrate, urea, ammonium bicarbonate, and potassium hydroxide; and the concentration of the base is 0.01-0.2 mol / L.

[0076] In certain embodiments of the present invention, in step S2, the rotation speed of the ultra-gravity reactor is 300-3000 rpm.

[0077] In certain embodiments of the present invention, in step S2, the feed flow rate of the peristaltic pump is 100-600 mL / min; and the feed flow rate ratio of the zirconium salt suspension B to the alkali solution A in the peristaltic pump is 100:75-100:200.

[0078] Example 1

[0079] A method for preparing hollow nano-zirconia under ultra-gravity conditions comprises the following steps:

[0080] S1. 8 ml of zirconium n-butoxide was dissolved in 100 ml of ethanol and stirred for 10 min to obtain a zirconium salt solution A. 10.776 g of nano calcium carbonate (particle size of 70-180 nm) was weighed, 2 ml of water and 100 ml of ethanol were measured, and the mixture was mixed and stirred for 10 min to obtain a suspension B.

[0081] S2. The zirconium salt solution A and the suspension B are simultaneously introduced into the high-gravity reactor through a peristaltic pump, the rotation speed of the high-gravity reactor is 500 rpm, and the feed flow rate of the peristaltic pump is 200 mL / min; the generated suspension C is collected from the outlet of the high-gravity reactor; the suspension C is centrifuged and washed with water for 3 times to obtain a filter cake D;

[0082] S3, drying the filter cake D at 60°C for 10 h and then heat treating it at 200°C for 1 h, washing it with sufficient 10% dilute hydrochloric acid for 5 h to remove the nano-calcium carbonate template, washing it with water by centrifugation for 3 times, and drying it at 60°C for 10 h to obtain hollow nano-zirconia with amorphous crystal phase;

[0083] This embodiment is a specific embodiment of the first technical solution of the present invention. In this embodiment, a nano calcium carbonate hard template with a particle size of 70-180nm is used, and the target product obtained is a hollow nano zirconium oxide powder with an average particle size of 150nm, a wall thickness of 12nm, and a complete hollow morphology and an amorphous crystal phase;

[0084] The transmission electron microscope image of the product of this embodiment is as follows Figure 1 As shown;

[0085] The X-ray diffraction pattern of the product in this embodiment is as follows Figure 2 As shown,

[0086] The nano calcium carbonate template used in the preparation process of the product of this embodiment is as follows Figure 3 shown.

[0087] Example 2

[0088] A method for preparing hollow nano-zirconia under ultra-gravity conditions comprises the following steps:

[0089] S1. 8 ml of zirconium n-butoxide was dissolved in 100 ml of ethanol and stirred for 10 min to obtain a zirconium salt solution A. 21.552 g of nano-calcium carbonate was weighed, 2 ml of water and 100 ml of ethanol were mixed and stirred for 10 min to obtain a suspension B.

[0090] S2. The zirconium salt solution A and the suspension B are simultaneously introduced into the high-gravity reactor through a peristaltic pump, the rotation speed of the high-gravity reactor is 500 rpm, and the feed flow rate of the peristaltic pump is 200 mL / min; the generated suspension C is collected from the outlet of the high-gravity reactor; the suspension C is centrifuged and washed with water for 3 times to obtain a filter cake D;

[0091] S3, drying the filter cake D at 60°C for 10 h and then heat treating it at 200°C for 1 h, washing it with sufficient 10% dilute hydrochloric acid for 5 h to remove the nano-calcium carbonate template, washing it with water by centrifugation for 3 times, and drying it at 60°C for 10 h to obtain hollow nano-zirconia with amorphous crystal phase;

[0092] This embodiment is a specific embodiment of the first technical solution of the present invention. In this embodiment, by increasing the dosage of the nano-calcium carbonate hard template, the target product obtained is a hollow nano-zirconium oxide powder with an average particle size of 130nm, a wall thickness of 9nm, a complete hollow morphology and an amorphous crystal phase.

[0093] The transmission electron microscope image of the product of this embodiment is as follows Figure 4 shown.

[0094] Example 3

[0095] A method for preparing hollow nano-zirconia under ultra-gravity conditions comprises the following steps:

[0096] S1. 8 ml of zirconium n-butoxide was dissolved in 100 ml of ethanol and stirred for 10 min to obtain a zirconium salt solution A; 5.388 g of nano-calcium carbonate was weighed, 2 ml of water and 100 ml of ethanol were measured, and the mixture was stirred for 10 min to obtain a suspension B;

[0097] S2. The zirconium salt solution A and the suspension B are simultaneously introduced into the high-gravity reactor through a peristaltic pump, the rotation speed of the high-gravity reactor is 500 rpm, and the feed flow rate of the peristaltic pump is 200 mL / min; the generated suspension C is collected from the outlet of the high-gravity reactor; the suspension C is centrifuged and washed with water for 3 times to obtain a filter cake D;

[0098] S3, drying the filter cake D at 60°C for 10 h and then heat treating it at 200°C for 1 h, washing it with sufficient 10% dilute hydrochloric acid for 5 h to remove the nano-calcium carbonate template, washing it with water by centrifugation for 3 times, and drying it at 60°C for 10 h to obtain hollow nano-zirconia with amorphous crystal phase;

[0099] This embodiment is a specific example of the method for preparing hollow nano-zirconia as described in claim 1. In this embodiment, by reducing the amount of nano-calcium carbonate template, the target product obtained is a hollow nano-zirconia powder with a particle size of 170nm, a wall thickness of 25nm, a complete hollow morphology and an amorphous crystal phase.

[0100] The transmission electron microscope image of the product of this embodiment is as follows Figure 5 shown.

[0101] Example 4

[0102] A method for preparing hollow nano-zirconia under ultra-gravity conditions comprises the following steps:

[0103] S1. 8 ml of zirconium n-butoxide was dissolved in 100 ml of ethanol and stirred for 10 min to obtain a zirconium salt solution A. 10.776 g of nano-calcium carbonate was weighed, 2 ml of water and 100 ml of ethanol were measured, and the mixture was mixed and stirred for 10 min to obtain a suspension B.

[0104] S2. The zirconium salt solution A and the suspension B are simultaneously introduced into the high-gravity reactor through a peristaltic pump, the rotation speed of the high-gravity reactor is 500 rpm, and the feed flow rate of the peristaltic pump is 200 mL / min; the generated suspension C is collected from the outlet of the high-gravity reactor; the suspension C is centrifuged and washed with water for 3 times to obtain a filter cake D;

[0105] S3, drying the filter cake D at 60°C for 10 h and then heat treating it at 200°C for 1 h, washing it with sufficient 10% dilute hydrochloric acid for 5 h to remove the nano-calcium carbonate template, washing it with water by centrifugation for 3 times, and drying it at 60°C for 10 h to obtain hollow nano-zirconia with amorphous crystal phase;

[0106] This embodiment is a specific example of the method for preparing hollow nano-zirconia as described in claim 1. In this embodiment, a nano-calcium carbonate hard template with a particle size of 50-100nm is used, and the target product obtained is a hollow nano-zirconia powder with an average particle size of 100nm, a wall thickness of 14nm, a complete hollow morphology and an amorphous crystal phase.

[0107] The transmission electron microscope image of the product of this embodiment is as follows Figure 6 shown.

[0108] Example 5

[0109] A method for preparing hollow nano-zirconia under ultra-gravity conditions comprises the following steps:

[0110] S1. 8 ml of zirconium n-butoxide was dissolved in 100 ml of ethanol and stirred for 10 min to obtain a zirconium salt solution A. 10.776 g of nano-calcium carbonate was weighed, 2 ml of water and 100 ml of ethanol were measured, and the mixture was mixed and stirred for 10 min to obtain a suspension B.

[0111] S2. The zirconium salt solution A and the suspension B are simultaneously introduced into the high-gravity reactor through a peristaltic pump, the rotation speed of the high-gravity reactor is 500 rpm, and the feed flow rate of the peristaltic pump is 200 mL / min; the generated suspension C is collected from the outlet of the high-gravity reactor; the suspension C is centrifuged and washed with water for 3 times to obtain a filter cake D;

[0112] S3, drying the filter cake D at 60°C for 10 h and then heat treating it at 200°C for 1 h, washing it with sufficient 10% dilute hydrochloric acid for 5 h to remove the nano-calcium carbonate template, washing it with water by centrifugation for 3 times, and drying it at 60°C for 10 h to obtain hollow nano-zirconia with amorphous crystal phase;

[0113] S4. calcining the amorphous hollow nano-zirconia at 700° C. for 3 h to obtain hollow nano-zirconia with a tetragonal crystal phase.

[0114] This embodiment is a specific embodiment of the method for preparing hollow nano-zirconia as claimed in claim 1. In this embodiment, the amorphous hollow nano-zirconia obtained in Example 1 is calcined at high temperature to obtain a tetragonal hollow nano-zirconia powder.

[0115] The X-ray diffraction pattern of the product in this embodiment is as follows Figure 7 shown.

[0116] Example 6

[0117] A method for preparing hollow nano-zirconia under ultra-gravity conditions comprises the following steps:

[0118] S1, weigh 0.6445g zirconium oxychloride and 1.2g nano carbon sphere template, dissolve them in 100ml water, and ultrasonically disperse them for 10min to obtain zirconium salt suspension A; weigh 0.5ml ammonia water and 100ml water, mix and stir for 10min to obtain alkali solution B;

[0119] S2, the zirconium salt solution A and the suspension B are simultaneously introduced into the high gravity reactor through a peristaltic pump, the rotation speed of the high gravity reactor is 500rpm, the peristaltic pump feed flow rate of the zirconium salt solution A is set to 200mL / min, and the peristaltic pump feed flow rate of the alkali solution B is set to 200ml / min; the generated suspension C is collected from the outlet of the high gravity reactor; the suspension C is centrifuged and washed with water for 3 times to obtain a filter cake D;

[0120] S3. Dry the filter cake D at 60° C. for 10 h and then calcine it at 700° C. for 3 h to obtain hollow nano-zirconia.

[0121] This embodiment is a specific example of the method for preparing hollow nano-zirconia as described in claim 2, and the target product obtained is a hollow nano-zirconia powder with an average particle size of 70 nm, a wall thickness of 8 nm, and a complete hollow morphology.

[0122] The transmission electron microscope image of the product in this embodiment is Figure 8 As shown;

[0123] The nano carbon sphere template used in the preparation process of the product in this embodiment is as follows Fig. 9 shown.

[0124] Example 7

[0125] A method for preparing hollow nano-zirconia under ultra-gravity conditions comprises the following steps:

[0126] S1, weigh 0.6445g zirconium oxychloride and 1.2g nano carbon sphere template, dissolve them in 100ml water, and ultrasonically disperse them for 10min to obtain zirconium salt suspension A; weigh 0.5ml ammonia water and 100ml water, mix and stir for 10min to obtain alkali solution B;

[0127] S2, the zirconium salt solution A and the suspension B are simultaneously introduced into the high gravity reactor through a peristaltic pump, the rotation speed of the high gravity reactor is 500rpm, the peristaltic pump feed flow rate of the zirconium salt solution A is set to 200mL / min, and the peristaltic pump feed flow rate of the alkali solution B is set to 200ml / min; the generated suspension C is collected from the outlet of the high gravity reactor; the suspension C is centrifuged and washed with water for 3 times to obtain a filter cake D;

[0128] S3. Dry the filter cake D at 60° C. for 10 h and then calcine it at 700° C. for 3 h to obtain hollow nano-zirconia.

[0129] This embodiment is a specific embodiment of the method for preparing hollow nano-zirconia as described in claim 2. In this embodiment, a nano-carbon sphere template with a larger particle size is used, and the target product obtained is a hollow nano-zirconia powder with a particle size of 200nm, a wall thickness of 15nm, and a complete hollow morphology.

[0130] The transmission electron microscope image of the product of this embodiment is as follows Fig.10 shown.

[0131] Comparative Example 1

[0132] Example 1 was repeated, except that in step S2, the reaction equipment used was a conventional stirred tank reactor instead of a supergravity reactor, and the reaction time was 30 min.

[0133] The zirconium oxide product prepared in this comparative example has a morphology of solid particles and hollow particles coexisting. Under the reaction conditions, due to the excessively high concentration of the zirconium salt solution, heterogeneous nucleation occurs. The transmission electron microscopy image of the prepared product is as follows: Fig.11 shown.

[0134] Comparative Example 2

[0135] Example 1 was repeated, except that in step S1, the concentration of the zirconium salt was 0.005 mol / L.

[0136] The nano zirconium oxide product prepared in this comparative example cannot form a complete hollow structure. Due to the low zirconium salt concentration, the hydrolysis rate of the zirconium salt is slowed down, and the template cannot be effectively coated. The transmission electron microscopy image of the prepared product is as follows: Fig.12 shown.

[0137] Comparative Example 3

[0138] Example 1 was repeated, except that in step S1, the molar ratio of water to zirconium salt in the suspension B was 26.4:1.

[0139] The nano-zirconia product prepared in this comparative example has a morphology of solid particles and hollow particles coexisting. Since the proportion of water used as the hydrolyzing agent is relatively high, the hydrolysis rate of the zirconium salt is increased, resulting in the occurrence of heterogeneous nucleation. The transmission electron microscope image of the prepared product is as follows: Fig.13 shown.

[0140] Comparative Example 4

[0141] Example 1 was repeated, except that in step S2, the washing solvent used in the washing was ethanol.

[0142] The nano-zirconia product prepared in this comparative example was severely broken and could not form an effective hollow structure. The transmission electron microscope image of the prepared product is shown in FIG. Fig.14 shown.

[0143] Comparative Example 5

[0144] Example 1 was repeated, except that in step S3, filter cake D was calcined at 700° C. for 3 h after drying, instead of first performing heat treatment and then calcining at 700° C. in steps S3 and S4.

[0145] The product prepared in this comparative example is not hollow nano-zirconia. Due to the high temperature during the calcination process, nano-calcium carbonate and zirconium oxide undergo a solid phase reaction, and finally a hollow and broken calcium zirconate is generated. The transmission electron microscope image of the prepared product is as follows Fig.15 The X-ray diffraction pattern is shown in Figure 16.

[0146] Comparative Example 6

[0147] Example 5 was repeated, except that in step S2, the reaction equipment used was a conventional stirred tank reactor instead of a supergravity reactor, and the reaction time was 30 min.

[0148] In this comparative example, a hollow zirconia product cannot be obtained. The prepared product is a product of agglomeration of zirconia nanoparticles. The transmission electron microscope image of the prepared product is as follows: Fig.17 shown.

[0149] Comparative Example 7

[0150] Example 5 was repeated, except that in step S1, the concentration of the zirconium salt was 0.2 mol / L.

[0151] The product prepared in this comparative example cannot form a complete hollow structure. Since the higher zirconium salt concentration accelerates the hydrolysis rate of the zirconium salt, the template cannot be effectively coated. The transmission electron microscopy image of the prepared product is as follows: Fig.18 shown.

[0152] Comparative Example 8

[0153] Example 5 was repeated, except that in step S1, the base was sodium hydroxide.

[0154] The product prepared in this comparative example is completely nano zirconium oxide particles. Due to the excessively strong alkali solution, the hydrolysis rate of the zirconium salt is accelerated, resulting in the occurrence of heterogeneous nucleation. The transmission electron microscope image of the prepared product is as follows: Fig.19 shown.

[0155] Comparative Example 9

[0156] Example 5 was repeated, except that in step S2, the ratio of the peristaltic pump feed flow rates of the zirconium salt solution A and the alkali solution B was 100:50.

[0157] The product prepared in this comparative example is hollow zirconia with an incomplete hollow morphology. Due to the small amount of alkali solution, the hydrolysis rate of the zirconium salt is slowed down, and the template cannot be effectively coated. The transmission electron microscopy image of the prepared product is as follows: Fig. 20 shown.

[0158] Obviously, the above embodiments and comparative examples of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the embodiments here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A method for preparing hollow nano zirconium oxide, characterized in that: The steps include: S1, dissolving a zirconium salt in an alcohol solvent to obtain a zirconium salt solution A; mixing a hard template, water, and an alcohol solvent to obtain a suspension A; S2, passing the zirconium salt solution A and the suspension A into a supergravity reactor through a peristaltic pump to achieve rapid mixing reaction, and then collecting the generated suspension B; filtering the suspension B, and washing with water to obtain a filter cake A; S3. After drying the filter cake A, heat it to 150-250° C. for heat treatment for 0.5-1.5 h, use sufficient acid with a concentration of 5-30% for pickling for 3-12 h, wash it with water, and obtain hollow nano zirconium oxide after drying.

2. The preparation method according to claim 1, characterized in that: In step S1, the zirconium salt is one or more of zirconium n-propoxide, zirconium isopropoxide, zirconium n-butoxide, and zirconium tert-butoxide; and the concentration of the zirconium salt is 0.02-0.1 mol / L.

3. The preparation method according to claim 1, characterized in that: In step S1, the alcohol solvent is one or more of methanol, ethanol, n-propanol, isopropanol, tert-butanol, and sec-butanol.

4. The preparation method according to claim 1, characterized in that: In step S1, the ratio of the amount of water to the amount of zirconium salt in the suspension A is 2:1-16:1; Preferably, in step S1, the hard template is one or more of nano-calcium carbonate, nano-magnesium carbonate, nano-lanthanum carbonate, nano-iron oxide, nano-aluminum oxide, nano-copper oxide, nano-zinc oxide, and nano-lanthanum hydroxide; Preferably, in step S1, the mass ratio of the hard template in the suspension A to the mass of the zirconium salt when completely converted to zirconium oxide is 10:0.1-10:

10.

5. The preparation method according to claim 1, characterized in that: In step S2, the rotation speed of the ultra-gravity reactor is 300-3000 rpm; Preferably, in step S2, the feed flow rate of the peristaltic pump is 100-600 mL / min; and the feed flow rate ratio of the zirconium salt solution A and the suspension A in the peristaltic pump is 100:75-100:

200.

6. The preparation method according to claim 1, characterized in that: In step S3, the acid is one or more of hydrochloric acid, nitric acid, acetic acid, and phosphoric acid.

7. A method for preparing hollow nano zirconium oxide, characterized in that: The steps include: S1, mixing a zirconium salt and a hard template, dissolving them in water to obtain a zirconium salt suspension B; mixing an alkali and water to obtain an alkali solution A; S2, passing the zirconium salt suspension B and the alkali solution A into the supergravity reactor through a peristaltic pump to achieve rapid mixing reaction, and then collecting the generated suspension C; washing the suspension C to obtain the filter cake B; S3. After drying the filter cake B, calcining it at 500-800° C. for 3-7 hours to obtain hollow nano zirconium oxide.

8. The preparation method according to claim 6, characterized in that: In step S1, the zirconium salt is one or more of zirconium oxychloride, zirconium chloride, zirconium acetate, zirconium acetylacetonate, zirconium oxynitrate, and zirconium sulfate; and the concentration of the zirconium salt is 0.01-0.05 mol / L.

9. The preparation method according to claim 6, characterized in that: In step S1, the hard template is one or more of nano-carbon spheres, nano-PS spheres, nano-PSA spheres, and nano-PMMA spheres; the mass ratio of the hard template in the zirconium salt suspension B to the mass ratio when the zirconium salt is completely converted into zirconium oxide is 10:0.1-10:

10.

10. The preparation method according to claim 6, characterized in that: In step S1, the base is one or more of ammonia water, hydrazine hydrate, urea, ammonium bicarbonate, and potassium hydroxide; the base concentration is 0.01-0.2 mol / L; Preferably, in step S2, the rotation speed of the high gravity reactor is 300-3000 rpm; Preferably, in step S2, the feed flow rate of the peristaltic pump is 100-600 mL / min; and the feed flow rate ratio of the zirconium salt suspension B to the alkali solution A in the peristaltic pump is 100:75-100:200.